Territorial Vulnerability and Accessibility to Proximity Services for Older People in the City of Valencia - Pitarch-Garrido, Maria Dolores; Fajardo-Magraner, Félix (Revista de Estudios Andaluces, 2019)
The increase in the average age of the population in Western societies is a reality that defines new parameters of coexistence as well as new social demands. In the case of the elderly, the services guarantee not only the care, in particular to the dependents, but also the company (loneliness). This article analyses the location and accessibility to these services, specifically day centres, municipal centres of activity and residences, in the city of Valencia, which is also of great interest for planning and public management. Emphasis is placed on the context of the most vulnerable neighbourhoods. The results indicate that there are clear differences according to the place of residence of the people, the public or private model of the offer and the type of transport, all of which lack social and spatial cohesion, despite the good general situation of the city.